Yoga Anak untuk Edukasi di TK As Solihah Bawen Semarang - Feny Marselina; Ida Sofiyanti; Siti Aisyah; Annisa; Vivin Mustikawati (Universitas Ngudi Waluyo, 2022)
Preschool children are children who are undergoing a process of growth and development. Based on the 2018 Riskesdas, a comparison of child development in children aged 36-59 months in Indonesia with a total development index of 88.3% was obtained, of which 64.6% were literate, 97.8% physical, 69.9% social-emotional, and 95.2%. learning. Today's children have varied activities ranging from school activities, extracurricular, tutoring and homework or even they are busy playing gadgets so that it makes them tired and stressed so they lack concentration. Stress that is allowed to drag on will be very dangerous for health because it will affect health, emotions, spirituality, and damage the whole self. This community service is carried out in 4 stages, namely the selection of preschool age children, licensing to the school, implementation of activities, evaluation. This dedication aims to provide education to teachers in the school about the importance of yoga for children. The population of this service is kindergarten students, totaling 54 children. This activity uses leaflet media and is carried out offline (face to face). AbstrakAnak prasekolah adalah anak yang sedang mengalami proses tumbuh dan kembang. Berdasarkan Riskesdas 2018 didapatkan perbandingan perkembangan anak pada anak usia 36-59 bulan di Indonesia dengan totalindeks perkembangan 88,3 %, dimana 64,6 % literasi, 97,8 % fisik, 69,9 % sosial emosional, dan 95,2 % learning. Anak anak zaman sekarang memiliki aktivitas bervariasi mulai dari kegiatan sekolah, eksktrakulkuler, les dan pr atau bahkan mereka sibuk bermain gadget sehingga membuat mereka kelelahan dan stress sehingga kurang konstentrasi. Stress yang di biarkan berlarut larut akan sangat berbahaya bagi kesehatan karena akan mempengaruhi kesehatan, emosi, spiritual, serta merusaka diri keseluruhan. Pengabdian masyarakat ini di lakukan dengan 4 tahapan yaitu pemilihan anak usia prasekolah, perizinan kepada pihak sekolah, pelaksanaan kegiatan, evaluasi. pengabdian ini bertujuan untuk memberikan edukasi kepada guru di sekeloh tentang pentingnya yoga bagi anak- anak. Populasi dari pengabdian ini adalah siswa TK yang berjumlah 54 anak. Kegiatan ini menggunakan media leaflet dan di lakukan secara luring (tatap muka).